2018
DOI: 10.3390/f9060320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought and Salinity on European Larch (Larix decidua Mill.) Seedlings

Abstract: Larix decidua, the European larch, is not normally affected by drought or salinity in its natural habitats, but it may be when grown as an ornamental tree, by the widespread practice of winter de-icing of mountain roads with NaCl, and because of global warming-induced environmental changes. The responses of two-month-old larch seedlings to 30 days water deficit (withholding irrigation) or salt stress (150 mM NaCl) treatments were studied by determining stress-induced changes in several growth parameters and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 83 publications
4
25
2
Order By: Relevance
“…In this study, the photosynthetic pigments contents of C. turczaninowii were not notably reduced at a salinity of 17~34 mM; however, salinities over 51 mM significantly reduced the content of Chl, and carotenoids after 42 days of treatment. This is consistent with previous reports on European Larch [49], Phragmites australis and Spartina alterniflora [50]. The photosynthetic apparatus of the plants was likely impaired and the chloroplast pigments were likely degraded under high salinity stress, thus inhibiting photosynthesis in the seedlings.…”
Section: Physiological Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the photosynthetic pigments contents of C. turczaninowii were not notably reduced at a salinity of 17~34 mM; however, salinities over 51 mM significantly reduced the content of Chl, and carotenoids after 42 days of treatment. This is consistent with previous reports on European Larch [49], Phragmites australis and Spartina alterniflora [50]. The photosynthetic apparatus of the plants was likely impaired and the chloroplast pigments were likely degraded under high salinity stress, thus inhibiting photosynthesis in the seedlings.…”
Section: Physiological Parameterssupporting
confidence: 92%
“…In Lavandula angustifolia, the same changes were found in SOD and POD activities at 25-100 mM salt concentrations [62]. While in European Larch seedlings, the SOD, APX, and GR activities were remarkable higher than the control at high salt stress (150 mM) [49], the results differed with ours. The increased antioxidant activity of enzymes under low salinity stress conditions suggests that the activation of an efficient free radical scavenging system can minimize the negative effects of peroxidation, thus contributing to the maintenance of membrane stability.…”
Section: Oxidative Stress and Antioxidant Mechanismscontrasting
confidence: 65%
“…For this reason, differences in stem length, fresh weight, or dry weight of plants submitted to stress treatments-in comparison to those from control-are optimal for ranking genotypes according to their degree of stress tolerance [44,45], but they are not always obvious when dealing with slow-growth woody species. However, European larch has a fast growing rate compared to other conifers [46] and effects of one month of drought stress could be noticed in the reduction of stem length growth, as also reported under salt stress [47]. Early diagnosis of stress suffered by plants is of great importance to minimize deleterious effects of prolonged droughts [48], but growth inhibition in a short time is difficult to assess in natural forest stands.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that 150 mM NaCl increased the MDA content and SOD activity in European larch needles (Larix decidua Mill. ), also suggesting that salinity induces oxidative stress that negatively impacts on plant growth (i.e., reduced the increases in stem length, fresh weight, and leaf water content compared with controls) [40]. Application of 24-epiBL modified the MDA content (reduced by 6.3%-27.6% in SS-S1 and 5.6%-39.8% in SS-S2), antioxidant enzyme activity (increased the activities of SOD and POD by 0.8%-12% and 39.4%-90.4%, respectively, compared with SS-S1 and by 1.4%-41% and 43.1%-116.8% compared with SS-S2, respectively).…”
Section: Antioxidative Effect In Leavesmentioning
confidence: 99%